2018
DOI: 10.1590/1414-431x20176698
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pathway cross-talks in ankylosing spondylitis through investigating the interactions among pathways

Abstract: Given that the pathogenesis of ankylosing spondylitis (AS) remains unclear, the aim of this study was to detect the potentially functional pathway cross-talk in AS to further reveal the pathogenesis of this disease. Using microarray profile of AS and biological pathways as study objects, Monte Carlo cross-validation method was used to identify the significant pathway cross-talks. In the process of Monte Carlo cross-validation, all steps were iterated 50 times. For each run, detection of differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, few studies have explored the role of mitochondria in AS. There are only analytical studies that have predicted that the pathway of mitochondrial dysfunction and some mitochondrion-related proteins may be involved with AS 46,47 . In this study, we explored mitochondrial function in AS and discovered that the AS serum environment induced mitochondrial dysfunction in MSCs and subsequently raised ROS levels and caused MSCs senescence.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have explored the role of mitochondria in AS. There are only analytical studies that have predicted that the pathway of mitochondrial dysfunction and some mitochondrion-related proteins may be involved with AS 46,47 . In this study, we explored mitochondrial function in AS and discovered that the AS serum environment induced mitochondrial dysfunction in MSCs and subsequently raised ROS levels and caused MSCs senescence.…”
Section: Discussionmentioning
confidence: 99%
“…The JNK and NF‐κB signaling pathways played vital roles in the regulation of inflammation . Previous studies had reported that JNK and NF‐κB pathways are activated in AS, and the two pathways are involved in the pathogenesis of AS . Li et al found that IL‐17 inhibited new bone formation through JNK and NF‐κB pathways.…”
Section: Discussionmentioning
confidence: 99%